1954
DOI: 10.1542/peds.14.5.505
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Congenital Malformations: A Study of 5,964 Pregnancies

Abstract: I. The plan is described of a prospective study of the outcome of 5,964 pregnancies, with special emphasis on the relationship of factors in fetal environment to the incidence of abortions, stillbirths, neonatal mortality and congenital malformations. II. Data are presented on the overall incidence of congenital malformations according to sex, race, weight at delivery, maternal age and order of birth. A. The incidence of congenital malformations among 5,739 products of conception … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

1960
1960
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(8 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…The EUROCAT reported that each year in the European Union, approximately 125,000 fetuses and infants of 5.0 million births (2.5%) have a congenital anomaly ( 37 ). Another study reported that the incidence of congenital malformations among 5,739 products of conception (weighing over 500 g) was 7.5%; the rate was 7.0% among infants born alive and surviving the neonatal period, 13.6% among antepartum deaths, 23.3% among intrapartum deaths, and 29.6% among neonatal deaths ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The EUROCAT reported that each year in the European Union, approximately 125,000 fetuses and infants of 5.0 million births (2.5%) have a congenital anomaly ( 37 ). Another study reported that the incidence of congenital malformations among 5,739 products of conception (weighing over 500 g) was 7.5%; the rate was 7.0% among infants born alive and surviving the neonatal period, 13.6% among antepartum deaths, 23.3% among intrapartum deaths, and 29.6% among neonatal deaths ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, once contact is made, the detection or recording of an anomaly does not automatically follow. For example, in a study in which physical examinations were performed at birth, 6 months, and 12 months, Mcintosh et al [11] found that of all 465 affected births eventually identified in their series, only 201 (43.2%) 'presented signs, symptoms and RG (roentgenographic) abnormalities which were observable at birth'.…”
Section: Definition Of Populationsmentioning
confidence: 99%
“…There is a range of possibilities for dealing with the problems of ascertainment and, in particular, underascertainment. One method is population screening, but follow-up studies have shown that cases are missed by this approach [6,11 ].…”
Section: The Quality Of the Diagnostic Datamentioning
confidence: 99%
“…Mediante programas de vacunación se ha tenido mucho éxito en la eliminación de esta enfermedad. Al año de edad, se coloca la vacuna trivalente: sarampión, rubéola y parotiditis y un refuerzo entre los 6 a 12 años 3,[13][14][15] . A las niñas adolescentes, no vacunadas y que no tienen antecedentes de haber tenido la enfermedad, se les coloca la vacuna monovalente antirubéola.…”
unclassified
“…Para su prevención, es importante difundir las medidas de higiene, para evitar el contagio de las embarazadas. Durante los controles médicos prenatales, realizar estudios seriados, con serología para el toxoplasma, en las mujeres en riesgo, efectuando tratamiento preventivo si hay seroconversión [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]18 .…”
unclassified